Research on the Strategy of Preservation and Utilization of Cultural Relics--Take the former site of the training institute for skilled workers in Nanman Army Arsenal as an example - Zhu Xiaofei; Wang He (E3S Web of Conferences, 2023)
The former site of the Training Institute for Skilled Persons in Nanman Army Arsenal is located on the campus of Dadong Vocational College in Shenyang, and it is the fifth batch of cultural relics protection units announced by Shenyang. Firstly, this paper gives a brief introduction to the “old site” buildings, and then summarizes the existing diseases of cultural relics buildings by means of on-site investigation and engineering surveying and mapping. Adhering to the tenet of “utilization is the best protection”, this paper focuses on the principles and strategies of protection and utilization of cultural relics buildings, so that cultural relics buildings can be well repaired and historical information and values can be better protected.